The Features of Guardian Activity with Children of Labour Migrants - Sabat, Natalia (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
The actuality of the problem of labour migration in modern Ukraine is examined in the article. The features of organization of guardian activity with children whose parents work abroad are analysed (its integrated character, the necessity of realization of guardianship both to a child and his nearest social surroundings and others). The basic constituents are described: the presence of profound knowledge of regularities of psychical development of a child and factors that promote forming its personality; the use of traditional and modern technologies of teaching courses of guardian pedagogy and educator’s guardian activity; the emotional-humanistic orientation on a child; the creation of moral-psychological comfort; the forming of culture of relations based on humanism principle, empathetic skills of communication; the adjusting of pedagogical mutual relations with parents or guardians. On the basis of analysis of works of home scientists the basic stages of work with such category of children are exposed, the most optimal forms and methods of work with them are distinguished. Attention is accented on the dominant role of a teacher in the process of giving a help to the children of labour migrants, the importance of collaboration of all educational institutions in this activity